실리콘 웨이퍼 비저항에 따른 Dopant-Free Silicon Heterojunction 태양전지 특성 연구 - 김성해(Sung Hae Kim); 이정호(Jung-Ho Lee) (Biuletyn Uniejowski, 2018)
Dopant-free silicon heterojunction solar cells using Transition Metal Oxide(TMO) such as Molybdenum Oxide($MoO_X$) and Vanadium Oxide($V_2O_X$) have been focused on to increase the work function of TMO in order to maximize the work function difference between TMO and n-Si for a high-efficiency solar cell. One another way to increase the work function difference is to control the silicon wafer resistivity. In this paper, dopant-free silicon heterojunction solar cells were fabricated using the wafer with the various resistivity and analyzed to understand the effect of n-Si work function. As a result, it is shown that the high passivation and junction quality when $V_2O_X$ deposited on the wafer with low work function compared to the high work function wafer, inducing the increase of higher collection probability, especially at long wavelength region. the solar cell efficiency of 15.28% was measured in low work function wafer, which is 34% higher value than the high work function solar cells.